THE MODERATING ROLE OF FINANCIAL LITERACY ON THE IMPACT OF BEHAVIORAL BIASES TOWARD INVESTMENT DECISIONS AMONG GENERATION Z IN INDONESIA - Wilson, Wilson; Candy, Candy; Suprapto, Yandi (Catholic University Musi Charitas, 2026)
Purpose : This study examines the influence of behavioral biases including anchoring bias herding bias loss aversion bias and mental accounting bias on investment decisions and evaluates the moderating role of financial literacy among Generation Z investors in Indonesia Design Methodology Approach : A quantitative survey approach was applied using data collected from Generation Z investors with prior investment experience Data analysis was conducted using Partial Least Squares Structural Equation Modeling with SmartPLS to assess direct and moderating effects Findings : Loss aversion and mental accounting biases show a significant positive effect on investment decisions while anchoring and herding biases show positive but not significant effects Financial literacy significantly moderates the relationship between anchoring bias and herding bias with investment decisions while no moderating effect is observed in the relationships involving loss aversion and mental accounting Practical Implications : Financial literacy demonstrates a selective role in mitigating behavioral biases particularly those related to heuristic driven decision making Therefore targeted financial education programs are required to improve rational investment behavior among Generation Z investors Originality Value : Evidence is provided that the effectiveness of financial literacy as a moderating mechanism depends on the type of behavioral bias thereby offering a more nuanced understanding of behavioral finance in emerging market investor settings